Implementasi Lubang Biopori dalam Mengurangi Genangan Air dan Meningkatkan Resapan Air Tanah Studi Kasus: di Lingkungan SMP Negeri 2 Salatiga - Lintang Ayu Citra Buana; Bintan Salsafillah; Muhammad Raafi Aldinofa Shodikhon; Umi Zahrotul Afifah; Andar Ifazatul Nurlatifah (STKIP HARAPAN BIMA, 2026)
Environmental problems in the form of water puddles still frequently occur in school environments, especially due to climate change that causes uncertainty in rainfall patterns. One effort that can be implemented to address this problem is the application of biopore infiltration holes. This study aims to determine the implementation of biopore infiltration holes and their impact on reducing water puddles and increasing groundwater infiltration in the school environment. This study used a qualitative method conducted at SMP Negeri 2 Salatiga from October to November 2025. The object of the study was the implementation of biopore infiltration holes in the school environment, while the research participants consisted of two teachers responsible for managing the biopore system. The research instruments included interview guidelines and observation sheets. Data collection was carried out through interviews, field observations, and secondary data in the form of rainfall reports of Salatiga City over the last five years. The data were analyzed using descriptive qualitative analysis techniques through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of biopore infiltration holes at SMP Negeri 2 Salatiga provided benefits in reducing water puddles and increasing groundwater infiltration, although the effectiveness was not yet optimal in several areas dominated by impermeable surfaces. Therefore, it is necessary to increase the number of biopore holes, provide more even distribution, and integrate them with the school drainage system so that the implementation of biopores can work more optimally.